Evaluation of Nutritional Care for HIV (Human Immunodeficiency Virus) Patients with Pulmonary Tuberkulosis - Rahmi Kartini Pertiwi; Endang Mulyani; Nazhif Gifari (Universitas Pendidikan Indonesia, 2023)
Introduction: Indonesia is one of the countries with the fastest HIV development in Asia. The cumulative number of cases from 2003 to 2013 was 108,600 cases. The national accumulation is estimated at 186,000 people living with HIV in 2010. Papua is an area with an expanding HIV prevalence of 2.4%. HIV (Human Immunodeficiency Virus) is a virus that attacks the body's immune system. Tuberculosis (TB) is a bacterial infection that is spread through droplets inhaled from the coughs or sneezes of an infected person. Nutritional status is an important factor of disease immunity and plays a role in the frequency and severity of infection by inhibiting immune function for HIV patients with pulmonary TB. Vulnerability in HIV patients with a nutritional status below normal is more easily infected with Mycobacterium tuberculosis. Based on cases of TB HIV coinfection during 2010-2017, there was an increase from 2,393 to 7,796. This study aimed to determine the enhancement of nutritional needs of patients during hospitalization.Method: This research method uses a descriptive case study. This research was conducted in July 2021 at the Rumah Sakit Umum Tangerang with a saturated sample.Result: The outcome of observations and interviews with nutritional care for five days, there was an improvement in appetite disorders with an initial fulfillment of 70% to achieve a nutritional intake of 100%, the feeding route with the NGT gradually became oral, as well as the texture of enteral food, then the texture of the combination of soft and enteral, thus regular enteral meals. The finding is that monitoring the compliance of nutrients gradually increase the need for daily intake, eating routes, and evolved eating texture.